Detecção de pistas de aeroporto em imagens orbitais utilizando morfologia matemática - Ishikawa, Aline Sayuri [UNESP]; Da Silva, Paulo Henrique Amorim [UNESP]; Silva, Erivaldo Antonio da [UNESP] (My University, 2005)
The Brazilian Cartography presents great deficiency in cartographic products updating. This form, Remote Sensins techniques together Digital Processing Images - DPI, are contributing to improve this problem. The Mathematical Morphology theory was used in this work. The principal function was the pruning operator. With its were extracted the interest features that can be used in cartographic process updating. The obtained results are positives and showed the use potential of mathematical morphology theory in cartography, mainly in updating.
Detection of the airports tracks in orbital images using mathematical morphology
Keywords: Cartographics feature; Digital image processing; Mathematical morphology; Remote sensins; Updating; Feature extraction; Image analysis; Mapping; Remote sensing; Cartographic features; Cartographic process updating; Pruning operators; Airport runways